Salivary Nitric Oxide and Alpha-Amylase as Indexes of Training Intensity and Load - Diaz, M. M.; Bocanegra, O. L.; Teixeira, R. R.; Soares, S. S.; Espindola, F. S. (International Journal of Sports Medicine, 2013)
This study examined the variation in salivary nitric oxide (NO), alpha-amylase (sAA) and serum markers of muscle injury during 21 weeks of training in elite swimmers. Samples of saliva and blood were collected once a month during 5 months from 11 male professional athletes during their regular training season. The variation in each marker throughout the 21 weeks was compared with the dynamics of training volume, intensity and load. Unstimulated whole saliva was assessed for NO and sAA whereas venous blood was assessed for lactate dehydrogenase, creatine kinase, and γ-glutamyltransferase. Nitric oxide and sAA showed a proportional response to the intensity of training. However, whereas the concentration of NO increased across the 21 weeks, the activity of sAA decreased. Similar variations in the concentration of NO and the markers of muscle injury were also observed. The higher concentration of NO might be attributed to changes in haemodynamics and muscle regenerative processes. On the other hand, autonomic regulation towards parasympathetic predominance might have been responsible for the decrease in sAA activity. These findings provide appealing evidence for the utilization of salivary constituents in sports medicine to monitor training programmes.
Keywords: biomarker; saliva; blood; exercise; sports training